Pelecehan Seksual Dalam Dunia Kerja Spg Rokok - Meilani Tri Hapsari (Program Studi Hubungan Masyarakat Politeknik LP3I, 2023)
Sexual harassment in Cigarette girls’ workplace. This study examines how the cigarette girls view their works and sexual harassment in the workplace, examines the form of sexual harassment that happen to them, how they react to it, and examines the background of the sexual harassment experienced by the cigarette girls in the workplace. The method used is qualitative approach of Phenomenology which examines the result of subject’s interview to the level of meaning. Data used in this study were obtained from verbal and non verbal language that was done by the cigarette girls during the interview and observation. Active cigarette girls in Bandung were selected as subjects of this study. The selected informants who experienced the phenomenon of sexual harassment were interviewed based on their willingness to be able to describe their experience consciously. Based on the researched that was done, it is concluded that cigarette girls viewed their works as a fun job with high requirement but has negative image to it. The cigarette girls understood that sexual harassment happens in the workplace as violence to the personal will to decide, verbal and non verbal language that shouldn’t be said, disrespectful action, and power abuse. Cigarette girls viewed the form of sexual harassments is through verbal language, non verbal language, and imaging. Cigarette girls’ on reactions to sexual harassment in accordance with the form of sexual harassment, through verbal and non verbal language. It was examined that there were two factors triggered the sexual harassment to cigarette girls, subject and victim; previous mindset of negative images attached to cigarette girls and negative behaviors done by several of them outside the context of their works triggered the sexual harassment to take place.